The current state of research on wind turbines in Costa Rica - Richmond-Navarro, Gustavo (2019)
The result of some interviews made to the main actors in the wind turbines field in Costa Rica, as well as a literature review are presented in the current work. First, an outline of the roll of wind power in the national electrical power system is given, then, the achievements in wind energy research in the academic field, the research centers and the business sector are pointed out. In the academic field, the wind turbine built in the 1990s at the Costa Rican Institute of Technology, points out, being the first aerogenerator manufactured in the country using modern technology. With regard to research centers, the details about Ad Astra Rocket’s wind turbine, built between 2012 and 2016, are given. In the business sector, an emphasis is made on the SkyTwister, which has been subject of research and development in Costa Rica for more than 10 years and has received multiple awards nationally and internationally. Summarizing, the current research in the field of wind turbines, is exclusively carried out by Carlos Acosta Nassar with the SkyTwister turbine, the company “Interdinámica Energía”, and the Costa Rica Institute of Technology through its Wind Power Research Lab (known in Spanish as LIENE).